Management Experience of Surgical Complications of Dengue Fever Patients at Hameed Latif Hospital, Lahore - Ahmad, Farooq; Nadeem, Ahmad; Faisal, Muhammad Saad; Shaukat, Mubasher; Siddique, Kashif (Annals of King Edward Medical University, 2014)
Abstract Objective: This study was designed to determine the frequency, pattern and management of surgical com-plications among patients with dengue fever. Design: Cross sectional study design was used. Settings: Hameed Latif Hospital, Lahore. Methods: From March - 2009 to December - 2011 total of 875 patients of dengue fever with positive anti-dengue immunoglobulin M (IgM) serology were inclu-ded in this study. Complete blood count, liver function test, blood urea, serum creatinin, serum amylase were determined in all patients admitted with the diagnosis of dengue fever. All the patients were evaluated for the presence of surgical complications by physical exami-nation and real time ultrasound abdomen. Patient had CT - abdomen and brain where it was required. Patients having surgical complications were managed in dengue ward and ICU with multidisciplinary approach. Data entry and analysis was done by using SPSS 16. Results: Among 875 patients with dengue fever, 491 (43.9%) patients were men and 384 (48.9%) were women with age range (18 - 70) years. Surgical com-plications were detected in 121 (13.8%) patients: acute cholecystitis in 46 (5.26%); acute pancreatitis in 19 (2.17%); injection abscess in 14 (1.6%); gastrointesti-nal bleed in 24 (2.74%); forearm compartment synd-rome in 3 (0.34%); abdominal compartment syndrome in 2 (0.23%) and acute appendicitis, 4 (0.46%) pati-ents. Cerebral bleed, retroperitoneal hematoma, abdo-minal wall hematoma and splenic rupture was seen among 3 (0.34%), 2 (0.23%), 3 (0.34%), and 1 (0.11%) patients, respectively. Out of 121 patients surgery was done in 20 (16.5%) patients while rest of 101 (83.5%) patients were managed conservatively. Two patients died. Conclusion: Surgical complications are common and should be suspected in every patient with dengue fever. Majority of surgical manifestations of dengue fever were managed conservatively however surgical intervention was done in certain cases with favorable outcome. Key words: Dengue hemorrhagic fever, Surgical complications, Management of DHF.